A phase II study of pegylated liposomal doxorubicin oxaliplatin and cyclophosphamide as second-line treatment in relapsed ovarian carcinoma. (1st January 2006) - Valerio, M. R.; Tagliaferri, P.; Raspagliesi, F.; Fulfaro, F.; Badalamenti, G.; Arcara, C.; Cicero, G.; Russo, A.; Venuta, S.; Guarneri, G.; Gebbia, N.
Abstract : We carried out a phase II nonrandomized study to examine the level of activity of oxaliplatin, pegylated liposomal doxorubicin, and cyclophosphamide in a patient population with relapsed ovarian cancer pretreated with platinum derivatives and paclitaxel. Patients received oxaliplatin (85 mg/m 2 ), pegylated liposomal doxorubicin (30 mg/m 2 ), and cyclophosphamide (750 mg/m 2 ). A total of 49 patients (39 assessable for toxicity and response) were enrolled in this trial. Neutropenia grade 3 was observed in six patients (15%) and anemia grade 3 in one patient (0.2%). Fatigue grade 1–2 occurred in 26 patients (66%), nausea/vomiting grade 1 in 23 patients (58%), and alopecia grade 1–2 in 19 patients (48%). Twenty-one (53%) patients experienced grade 1–2 peripheral neuropathy. The overall response rate was 46% (95% CI 23.6–68.7). Median progression-free survival was 28 weeks (range 12–52 weeks) and median survival was 45 weeks (range 26–136+ weeks). The mean duration of response was 34 weeks (range 16–52 weeks). In platinum-resistant and -refractory ovarian cancer patients, the overall response rate was 37% (CI 95% 14.4–60.8) with a progression-free survival of 28 weeks (range 12–52 weeks) and a median survival of 42 weeks (range 28–84 weeks). This combination chemotherapy is generally well tolerated and is an active second-line regimen against ovarian cancer.